2000
DOI: 10.1046/j.1439-0264.2000.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Inhibin and Steroidogenic Enzymes in the Ovary of Common Tree Shrew (Tupaia glis) and Northern Smooth‐tailed Tree Shrew (Dendrogale murina)

Abstract: To study the ovarian function of the Order Scandentia, the localization of inhibin and steroidogenic enzymes (3 beta-hydroxysteroid dehydrogenase/isomerase and aromatase) in the ovaries of common tree shrew (Tupaia glis) and northern smooth-tailed tree shrew (Dendrogale murina) was immunohistochemically analysed. As in the results reported for other mammals, inhibin alpha-chain was localized in the follicular epithelium of secondary or Graafian follicles in the two species. The localization of aromatase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, as mentioned above, the expression of P450 aromatase was not restricted in the granulosa cells of all mammalian species. In the porcine ovary, P450 aromatase is expressed in both types of cells [17] and in that of tree shrews, it is only expressed in the thecal cell layer [18]. The results in chickens and leopard geckos may not reflect the characteristics of birds and reptiles, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, as mentioned above, the expression of P450 aromatase was not restricted in the granulosa cells of all mammalian species. In the porcine ovary, P450 aromatase is expressed in both types of cells [17] and in that of tree shrews, it is only expressed in the thecal cell layer [18]. The results in chickens and leopard geckos may not reflect the characteristics of birds and reptiles, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…5). It is reported that P450 aromatase was expressed in the granulosa cells in mammalian species [14][15][16] with a few exceptions [17,18]. In the ovary of chickens, however, it is reported that immunoreactivity for P450 aromatase was absent in the granulosa cell layer but was present in the theca cell layer [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunohistochemical technique was based on our previous reports (Kimura et al ., 1997;Nishiyama et al ., 1999). Paraffin was removed by xylene and the sections were treated in a 5% solution of normal goat serum to prevent background staining.…”
Section: Methodsmentioning
confidence: 99%